Numerical and Experimental Investigations of Micro Thermal Performance in a Tube with Delta Winglet Pairs - Jiangbo Wang; Ting Fu; Liangcai Zeng; Guang Chen; Fue-sang Lien (Micromachines, 2021)
In this research, a novel vortex generator (VG) is presented. The experimental and numerical investigations were carried out to study the micro thermal-hydraulic performance in a heated tube. The numerical results showed that the fluid in the core flow region and the near-wall region was fully mixed because of the longitudinal vortices created by the vortex generators. In addition, the experimental results showed that the heat transfer coefficient (<semantics>h</semantics>) decreased with the increasing pitch ratio (<semantics>PR</semantics>) value, while the friction coefficient exhibited the opposite trend. With the increasing ration angle (<semantics>RA</semantics>) numbers, the <semantics>h</semantics> values decreased while the <semantics>f</semantics> numbers increased. In addition, the maximum and minimum values of the fraction ratio were 1.66 and 4.27, while these values of the Nusselt number ratio were 1.24 and 1.83. The maximum thermal enhancement factor (TEF) was 1.21 when <semantics>PR </semantics>= 0.5, <semantics>RA </semantics>= 0° and <semantics>Re </semantics>= 9090. The heat transfer enhancement mechanism of the vortex generator is explained from the microscopic point of view.